Health promotion of adolescents in the rural context: a photovoice study. - Anny Giselly Milhome da Costa; Neiva Francenely Cunha Vieira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Living in rural areas and/or rural laying is considered a determiner factor of adolescents' social vulnerability . The objective of this study is: to analyze the adolescents' views of rural health based on the process of listening/speech/reflection. It is a Community-Based Participatory Research (CBPR) with a qualitative approach, which had as theoretical reference the Critical Education of Paulo Freire linked to Social Documentary Photography. The participants will be twenty-six adolescents between 12 and 18 years old who live in a rural area of Ceará, Brazil. The data collection will be carried out through the photovoice method, in which the participants receive cameras and catch images about their health reality.  The phases of the study will be: publication/selection of participants, 15 group meetings and data analyses. When we know the adolescents' view of rural health, we will be able to promote a process of critical reflection in groups and to generate proposals for solutions of local problems.